A systematic review and meta‐analysis of prospective transition from major depression to bipolar disorder. (18th January 2017) - Ratheesh, A.; Davey, C.; Hetrick, S.; Alvarez‐Jimenez, M.; Voutier, C.; Bechdolf, A.; McGorry, P. D.; Scott, J.; Berk, M.; Cotton, S. M.
Abstract : Objective: Some people with major depressive disorder (MDD) may be at a pre‐onset stage for bipolar disorder (BD), where early identification or prevention efforts may be feasible. We aimed to identify rates and characteristics predictive of transition to BD in prospective follow‐up studies of people with MDD. Methods: Using a systematic search strategy, we identified studies with a diagnostic ascertainment of MDD and BD of an adequate standard, and where the minimum length of follow‐up was 6 months. We examined the incidence and point prevalence of BD and the pooled odds ratios (OR) for baseline predictors. Results: From 5554 unique publications, 56 were included. Nearly a quarter of adults (22.5%) and adolescents with MDD followed up for a mean length of 12–18 years developed BD, with the greatest risk of transition being in the first 5 years. The meta‐analysis identified that transition from MDD to BD was predicted by family history of BD (OR = 2.89, 95% CI: 2.01–4.14, N = 7), earlier age of onset of depression ( g = −0.33, SE = 0.05, N = 6) and presence of psychotic symptoms (OR = 4.76, 95% CI: 1.79–12.66, N = 5). Conclusions: Participants with the identified risk factors merit closer observation and may benefit from prevention efforts, especially if outcomes broader than BD are considered.